2018
DOI: 10.1136/heartjnl-2018-313351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of apixaban compared with warfarin on coagulation markers in atrial fibrillation

Abstract: ObjectivesCompare the effect of apixaban and warfarin on coagulation and primary haemostasis biomarkers in atrial fibrillation (AF).MethodsThe biomarker substudy from the Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation trial included 4850 patients with AF randomised to treatment with apixaban or warfarin. Sixty per cent of patients used vitamin K antagonist (VKA) within 7 days before randomisation. Prothrombin fragment 1+2 (F1+2), D-dimer, soluble CD40 ligand (sCD40L) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
1
14
0
2
Order By: Relevance
“…Among OACs, it is reasonable to hypothesize that using an effective anticoagulant therapeutic strategy may suppress D-dimer levels to a greater degree, which could further reduce the risk of stroke in patients with elevated D-dimer levels [7,8,11]. Previous studies reported that NOACs were more efficient in reducing D-dimer levels than warfarin [7,8]. However, no studies have investigated the efficacy of NOACs versus warfarin in patients with AF-related stroke and atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among OACs, it is reasonable to hypothesize that using an effective anticoagulant therapeutic strategy may suppress D-dimer levels to a greater degree, which could further reduce the risk of stroke in patients with elevated D-dimer levels [7,8,11]. Previous studies reported that NOACs were more efficient in reducing D-dimer levels than warfarin [7,8]. However, no studies have investigated the efficacy of NOACs versus warfarin in patients with AF-related stroke and atherosclerotic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not collect detailed information on the changes in D-dimer levels after antithrombotic treatment during follow-up. Third, D-dimer value could change over time and be affected by anticoagulation or thrombolytic therapy [7,8,11]. There are different methods and time points to measure D-dimer levels, which may lead to substantial variations in the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HT has been underexplored in non-AF patients; the majority of AIS patients are non-AF patients [ 15 , 16 ] and they could also develop HT. Meanwhile, AF and medication for AF would influence hemostasis functions [ 17 , 18 ]. Thus, the risk factors of non-AF patients to develop HT after AIS need to be further explored, especially hemostasis functions.…”
Section: Introductionmentioning
confidence: 99%
“…However, HT has been underexplored in non-AF patients; the majority of AIS patients are non-AF patients [14,15] and they could also develop HT. Meanwhile, AF and medication for AF would in uence coagulation functions [16,17].Thus, the risk factors of non-AF patients to develop HT after AIS needs to be further explored, especially coagulation functions.…”
Section: Introductionmentioning
confidence: 99%